Pengaruh Social Media Marketing, Influencer Marketing, dan Kualitas Produk Terhadap Keputusan Pembelian Skincare Avoskin di Kota Bogor: Studi Media Tik-Tok pada Gen Z Kota Bogor - Lestari Indah Permai; Elang Ilik Martawijaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of social media marketing, influencer marketing, and product quality on the purchasing decisions of Avoskin skincare products among Generation Z in Bogor City. Employing a quantitative approach and Partial Least Square-Structural Equation Modeling (PLS-SEM) with 100 respondents, the findings reveal that influencer marketing and product quality significantly and positively affect purchasing decisions, while social media marketing has no significant impact. These results suggest that despite the popularity of social media, trust in influencers and perceptions of product quality play a more critical role in shaping consumer decisions. The study offers practical implications for beauty industry players to prioritize collaborations with influencers and the enhancement of product quality in their marketing strategies.